HCV Treatment Initiation in Patients with Chronic Kidney Disease: Results from ERCHIVES. (4th October 2017) - Butt, Adeel; Ren, Yanjie; Puenpatom, Amy; Arduino, Jean Marie; Kumar, Ritesh; Abou-Samra, Abdul-Badi
Abstract: Background: Newer directing antiviral agents against HCV (DAAs) are safe and efficacious in persons with chronic kidney disease (CKD). Whether availability of these newer DAAs has resulted in more persons with CKD initiating HCV treatment remains unknown. Methods: We identified HCV+ persons in ERCHIVES. We excluded HIV+ and HBsAg+ and those with missing HCV RNA and eGFR data. We determined the CKD stage according to National Kidney Foundation criteria. We determined the number of persons initiated on any of the approved DAA-regimen (defined as >14 days of DAA prescription). Logistic regression analyses was used to determine factors associated with treatment initiation. Results: Among 76, 513 evaluable persons, 21.1% initiated DAA treatment. Initiation rates differed significantly by CKD stage: 21.1% (15, 136/68, 469) for eGFR>90mL/minute/1.73m 2 and CKD stage-2; 14.0% 9853/6, 086) for CKD stage 3; and 7.6% (148/1, 958) for CKD stage-4/5. Those with CKD stage-3 were 35% less likely and those with CKD stage-4/5 were 65% less likely to initiate treatment with a DAA compared with those with baseline eGFR>90mL/minute/1.73m 2 . Those with Body Mass Index (BMI)>30 were more likely to initiate treatment (OR 1.24, 95% CI 1.19, 1.29). Treatment initiation was less likely in HCV genotype 2 or 3 and those with diabetes (OR 0.82, 95% CI 0.78, 0.86), cardiovascular disease (OR 0.73, 95% CI 0.68, 0.78), alcohol abuse or dependence (OR 0.75, 95% CI 0.72, 0.78) or cirrhosis (OR 0.85, 95% CI 0.80, 0.89) at baseline. Conclusion: Persons with more advanced CKD are less likely to receive treatment for HCV. Strategies are needed to improve treatment rates in the HCV/CKD population. Disclosures: A. Butt, Merck: Investigator, Grant recipient. A. Puenpatom, Merck: Employee, Salary. J. M. Arduino, Merck: Employee, Salary. R. Kumar, Merck: Employee, Salary